Monoclonal antibody based in vitro potency assay as a predictor of antigenic integrity and in vivo immunogenicity of a Respiratory Syncytial Virus post-fusion F-protein based vaccine. Issue 12 (14th March 2018) - Djagbare, Matieyendou Didier; Yu, Li; Parupudi, Arun; Sun, Jenny; Coughlin, Melissa L.; Rush, Benjamin S.; Sanyal, Gautam
Highlights: The basis of immunogenicity of Respiratory Syncytial Virus (RSV) Fusion (F) protein (RSVsF) based vaccine is addressed. An in vitro relative potency (IVRP) assay is a sensitive indicator of RSVsF antigen integrity. IVRP is a conservative predictor of in vivo immunogenicity elicited by RSVsF. Site A epitope of RSVsF showed greater stability against stress conditions than site C. These results have potential impact on development of recombinant protein based vaccines. Abstract: The post-fusion form of Respiratory Syncytial Virus (RSV) fusion (F) protein has been used recently in clinical trials as a potential vaccine antigen with the objective of eliciting protective immune response against RSV. In this paper, in vitro antigenicity and in vivo immunogenicity of recombinant, soluble F protein of RSV (RSVsF) were evaluated by several assays. In Vitro Relative Potency (IVRP) of RSVsF was measured in a sandwich ELISA using two antibodies, each specific for epitope site A or C. Therefore, IVRP reflected the integrity of the antigen in terms of changes in antibody binding affinity of either or both of these sites. RSVsF samples with a wide range of IVRP values were generated by applying UV irradiation (photo) and high temperature (heat) induced stress for varying lengths of time. These samples were characterized in terms of stress induced modifications in primary and secondary structures as well as aggregation of RSVsF. Immunogenicity, also referred to as In vivo potency, was measured by induction of total F-protein specific IgG and RSV-neutralizing antibodies in mice dosed with these RSVsF samples. Comparison of results between IVRP and these immunogenicity assays revealed that IVRP provided a sensitive read-out of the integrity of epitope sites A and C, and a conservative and reliable evaluation of the potency of RSVsF as a vaccine antigen. This high throughput and fast turn-around assay allowed us to efficiently screen many different RSVsF antigen lots, thereby acting as an effective filter for ensuring high quality antigen that delivered in vivo potency. In vitro and in vivo potencies were further probed at the level of individual epitope sites, A and C. Results of these experiments indicated that site A was relatively resistant to stress induced loss of potency, in vitro or in vivo, compared to site C.